Participation and Well Being Among Children and Youth With Childhood Onset Disabilities - Anaby, Dana; Granlund, Mats (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Participation, defined as involvement in life situations, is important for children's health and development. This Special Issue advances the knowledge about participation interventions and outcomes for children with disabilities in different settings and includes the perspectives of clinicians, families, and children. This is a collection of research from across the globe that advances knowledge in the following areas: - Participation interventions; - Measurement/assessment of participation outcomes; - Participation of special populations (i.e., ABI, ADHD, and ASD); and - Impact of participation on health and well being.